Laribacter hongkongensis: clinical presentation, epidemiology and treatment. A review of the literature and report of the first case in Denmark. Issue 6 (3rd June 2018) - Engsbro, Anne Line; Nielsen, Karen Leth; Hornum, Mads; Andersen, Leif Percival
Abstract: Background: Laribacter hongkongensis is an emerging pathogen related to gastroenteritis that can cause invasive and even fatal disease. The aim of this review is to describe the clinical presentation, epidemiology, treatment options and implications for the clinical microbiology laboratory. Methods: We searched Pubmed using the term Laribacter hongkongensis with limitations human and language English, and identified 35 publications with eight reports on human cases. Results: We describe our first case of prolonged, travel-related gastroenteritis where Laribacter hongkongensis was isolated as the sole pathogen. Our review suggests that L. hongkongensis causes non-bloody acute diarrhoea with potential for invasive disease, since three cases of bacteraemia and one case of dialysis related peritonitis have been described previously. L. hongkongensis has primarily been described in Asia, but reports from Europe, North America and Australia suggests a worldwide distribution. Broad culturing with subsequent identification by the MALDI-TOF is the current strategy for detection of L. hongkongensis . Phenotypic susceptibility testing is necessary to guide the treatment choice. Few resistance genes have been described in L. hongkongensis . Conclusion: L. hongkongensis should be considered a potential cause of acute and prolonged diarrhoea. Clinicians must be aware of the test methods in the local clinical microbiology laboratory, since L. hongkongensis is difficult to detect and easily overlooked.